Penyuluhan Kesehatan Cegah Stunting dengan Perbaikan Pola Makan, Pola Asuh Dan Sanitasi pada Ibu Hamil di UPT Puskesmas Antang - Nour Sriyanah; Suradi Efendi; Nurmaulida N; Zulfadhilah Z; Rahmawati R (PT.Mantaya Idea Batara, 2021)
: Stunting is a chronic malnutrition problem caused by lack of nutritional intake for a long time, resulting in growth disorders in children, namely the child's height is lower or shorter (short) than the standard age. The condition of a child's short body is often said to be a hereditary factor (genetic) from both parents, so that many people just accept it without doing anything to prevent it. In fact, as we all know, genetics is a determinant of health that has the least effect when compared to behavioral, environmental (social, economic, cultural, political) factors and health services. In other words, stunting is a preventable problem. Stunting is a growth failure problem experienced by infants under 5 years of age who are malnourished since in the womb until the baby is born. Assessment of stunting nutritional status can be done through anthropometric measurements of TB/U classified through nutritional classification status. Stunting is a condition where the child's height is shorter than the height of children his age. According to UNICEF, stunting occurs in children aged 0 to 59 months with a height below minus (moderate and severe stunting) and minus three (chronic stunting) measured from the WHO child growth standards. In Indonesia, stunting is still a health problem in quite a large number. Based on the 2013 Basic Health Research, around 37.2 percent of Indonesian children under the age of 5 are stunted.